Sustainability Report Dari Perspektif Teori Stewardship - Zul Azmi; Natasha Nadira Putri; Siti Aisah (CV. ITTC INDONESIA, 2026)
This study aims to examine the application of Stewardship Theory in sustainability research, particularly in explaining management commitment to sustainability practices and corporate reporting. This study employs a Systematic Literature Review (SLR) method based on the PRISMA guidelines by reviewing relevant scholarly articles published between 2020 and 2025. Eight selected articles were thematically analyzed to identify dominant discussion patterns, theoretical perspectives, and contextual factors influencing the application of Stewardship Theory in sustainability reporting and integrated reporting. The findings indicate that Stewardship Theory is widely used to explain long-term orientation, collective values, and ethical responsibility of management in supporting sustainability practices. In addition, the quality and consistency of sustainability reporting are influenced by corporate governance, management commitment, stakeholder pressure, and regulatory frameworks. This study confirms that Stewardship Theory is a relevant theoretical framework for explaining long-term-oriented corporate sustainability practices.